Analisis perbandingan rencana strategis Baitul Maal wat Tamwil dalam optimalisasi layanan pelanggan: (Pada studi kasus: BMT Maslahah, BMT Muamalah Mandiri, BMT Surya Barakah) - Huda, Muhammad Alamul; Akbar, Yodi Alrizky; Firdaus, Hafiz Hasbi (Maliki Interdisciplinary Journal, 2024)
This article was created with the aim of exploring the business strategies of THREE BMTs, namely BMT Maslahah, BMT Muamalah, and BMT Surya Barokah by analyzing strategic plans and market strategies. This research provides insightful information regarding the marketing strategies of each BMT. BMT Maslahah is known as the market leader in Baitul Maalwat Tamwil in the Pasuruan area and provides products that meet customer needs at various stages of life. BMT Muamalah Mandiri was founded with the aim of becoming a trusted sharia financial institution in providing excellent service to its customers. BMT Surya Berkah was founded with the aim of becoming a leading sharia financial institution that provides comprehensive and innovative financial services to its customers. So the aim of the three strategic plans is to provide financial services based on sharia principles and meet the economic needs of its customers.